Effect of butorphanol on opioid-induced cough: a meta-analysis of randomized controlled trials - Zhang J; Miao S; Tu Q; Shi M; Zou L; Liu S; Wang G (Dove Medical Press, 2018)
Jian Zhang,1,* Shuai Miao,2,* Qing Tu,3 Mengzhu Shi,2 Lan Zou,2 Su Liu,2 Guanglei Wang2 1Department of Anesthesiology, The Third People’s Hospital of Chengdu, Chengdu, Sichuan, China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, China; 3Department of Anesthesiology, Tangshan People’s Hospital, North China University of Science and Technology, Tangshan, Hebei, China *These authors contributed equally to this study Objective: The aim of this study was to assess the effect of butorphanol on the prevention of opioid-induced cough by a meta-analysis.Materials and methods: We searched PubMed, Embase, The Cochrane Library, and the China National Knowledge Infrastructure database for relevant randomized controlled trials (RCTs) to demonstrate the efficacy of butorphanol on the prevention of opioid-induced cough. We used RevMan 5.3 to conduct a meta-analysis on each outcome.Results: Eight RCTs comparing 942 patients were included in this study. The pooled meta-analysis showed that the incidence of opioid-induced cough in the butorphanol group was significantly decreased compared with that of the control group (risk ratio [RR]=0.17, 95% CI [0.09, 0.33], P<0.00001). Incidences of opioid-induced cough in the butorphanol group resulting in mild cough (RR=0.30, 95% CI [0.11, 0.78], P=0.01), moderate cough (RR=0.08, 95% CI [0.03, 0.22], P<0.00001), or severe cough (RR=0.08, 95% CI [0.02, 0.30], P=0.0001) were significantly lower than those of the control group.Conclusion: This meta-analysis suggested that butorphanol can effectively prevent the incidence of opioid-induced cough and reduce the severity of opioid-induced cough. Keywords: butorphanol, opioid, cough, meta-analysis, randomized controlled trial